Direct medical cost of COVID-19 in children hospitalized at a tertiary referral healthcare center in Mexico City - Reyes-López, Alfonso; Jimenez-Juárez, Rodolfo Norberto; Salinas-Escudero, Guillermo; Avilés-Robles, Martha Josefina; Martínez-Valverde, Silvia; Granados-García, Víctor; Garduño-Espinosa, Juan (Frontiers in Public Health, 2023)
Introduction: Despite the end of the COVID-19 pandemic being declared by the WHO, its economic consequences are far from over. One of these implications was the cost of inpatient care for health institutions, where some studies about the economic burden of COVID-19 in adult population were published with only a few focused on child population. Objective: To estimate the direct medical costs of COVID-19 in Mexican children. Method: Data about resources consumed during hospital stay were extracted from the medical records of patients hospitalized at a Mexican tertiary healthcare institution. Other sources of information were the unit prices of inputs and the salaries of health personnel, alongside using micro-costing methodology to obtain cost results by age groups over different hospital areas. Data analysis was performed with descriptive statistics and regression models to evaluate the predictors of total cost. Results: One hundred and ten medical records were reviewed of which 57.3% corresponded to male and the mean age was 7.2 years old; the estimated average cost per patient was US5,943 (95% CI: US4,249 - 7,637). When the costs of the three clinical areas were summed, only the group 5 – 10 years old showed a maximum cost of US14,000. The regression analysis revealed the following factors as significant: sex, age, staying at emergency room, having a positive bacterial culture, and having comorbidities. Discussion: The costs results were somewhat similar to those reported in children from the USA, but only regarding to low severity COVID-19 cases. However, comparability between this type of studies should be done with caution since the huge differences among healthcare systems of countries. The study cost results may help public decision-makers in budget planning and as inputs for future cost-effectiveness studies about interventions regarding COVID-19.